OMNI-CHANNEL STRATEGY TO INCREASING INTEREST REPURCHASING WITH GROWING FOCUS IN CONSUMER SATISFACTION FOR SOMETHING PRODUCTS: AN EMPIRICAL STUDY AT SUN PLAZA SHOPPING CENTER MEDAN - Shabrina Tifani; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring; Paham Ginting; Parapat Gultom (Universitas Efarina, 2023)
This research aims to see the influence of omnichannel strategy on repurchase interest through consumer satisfaction with Somethinc products at Sun Plaza Medan. The type of research used is quantitative research. The population in this study were 154 consumers who had purchased Somethingnc products. The sample size was drawn using non-probability sampling using the purposive sampling method. The data used are primary data and secondary data obtained through a list of statements and documentation studies. The data analysis technique uses structural equation modeling (SEM) with the Smart PLS 3.3 analysis tool. The research results directly show that omnichannel strategy has a positive and significant effect on repurchase interest, omnichannel strategy has a positive and significant effect on consumer satisfaction, customer experience has a positive and significant effect on repurchase interest. Consumer satisfaction has a positive effect on repurchase interest. Then the results of tests carried out indirectly show that tourist satisfaction is not able to mediate the relationship between omnichannel strategy and repurchase interest, but consumer satisfaction is able to mediate the relationship between customer experience and repurchase interest.